Scooby-doo! and the fairground phantom - Gelsey, James frey50 (New York : Scholastic Inc., 2000)
"The gang is having fun at the country fair. Shaggy and Scooby get in the spirit by judging baking contests and chili cook-offs..."
At head of title: Cartoon Network.
78588
Keywords: Mystery and detective stories; Dogs -- Fiction